A comprehensive review on the influence of light on signaling cross-talk and molecular communication against phyto-microbiome interactions. (3rd April 2021) - Shah, Anshuman; Tyagi, Shaily; Saratale, Ganesh Dattatraya; Guzik, Urszula; Hu, Anyi; Sreevathsa, Rohini; Reddy, Vaddi Damodara; Rai, Vandna; Mulla, Sikandar I.
Abstract: Generally, plant growth, development, and their productivity are mainly affected by their growth rate and also depend on environmental factors such as temperature, pH, humidity, and light. The interaction between plants and pathogens are highly specific. Such specificity is well characterized by plants and pathogenic microbes in the form of a molecular signature such as pattern-recognition receptors (PRRs) and microbes-associated molecular patterns (MAMPs), which in turn trigger systemic acquired immunity in plants. A number of Arabidopsis mutant collections are available to investigate molecular and physiological changes in plants under the presence of different light conditions. Over the past decade(s), several studies have been performed by selecting Arabidopsis thaliana under the influence of red, green, blue, far/far-red, and white light. However, only few phenotypic and molecular based studies represent the modulatory effects in plants under the influence of green and blue lights. Apart from this, red light (RL) actively participates in defense mechanisms against several pathogenic infections. This evolutionary pattern of light sensitizes the pathologist to analyze a series of events in plants during various stress conditions of the natural and/or the artificial environment. This review scrutinizes the literature where red, blue, white, and green light (GL) act as sensory systems that affects physiological parameters in plants. Generally, white and RL are responsible for regulating various defense mechanisms, but, GL also participates in this process with a robust impact! In addition to this, we also focus on the activation of signaling pathways (salicylic acid and jasmonic acid) and their influence on plant immune systems against phytopathogen(s).